A comparative study on campus sustainability in higher education sector in Hong Kong and Finland - Law, Cheuk Yan (2015)
This thesis presents a comparative study examining the practices of campus sustainability in Higher Education Sectors between Hong Kong and Finland. Campus sustainability is a trend during the last decade as a result of numerous declarations and meetings for sustainable development in Higher education all over the world. In this thesis, the investigated areas are focused on environmental sustainability and Social sustainability. This study used the content analysis method to analyze public available documents from the selected fifteen Higher education institutions in Hong Kong and Finland. The first stage was a description of the current overall situations of campus sustainability in the two regions. The descriptions are based on the three categories: Green Campus, Energy conservation and efficiency, Sustainability teaching and research. Sustainability reports, environmental reports and sustainability WebPages from the universities from Year 2007 to 2014 are examined. The second stage is a comparative study based on the findings in stage one, to derive the strengths and weaknesses in campus sustainability practices in the two regions. The last stage is to provide recommendations to higher education sectors to improve the weaknesses and hence develop better practices. The results show that higher education institutions in both regions are working towards campus sustainability. The practices are generally covered all the three categories but main focus areas are various from institutions. The weaknesses in campus sustainability practice in Hong Kong are in the area of renewable energy, staff training and involvement , and external collaborations in research, while that in Finland are Green building, involvement to society and sustainability publications. This thesis make some contributes by providing the overall pictures for campus sustainability in Hong Kong and Finland, which is valuable for governmental and education sectors for future planning; and also the detailed information for individual institutions to learn from each other in the good practices.